Levels Of Depression And Anxiety In Mexican Health Workers Hospital Belisario Domínguez - Martinez-Lanz, Patricia; Navarro Robles, José; Carlos, Fuentes; L´Gámiz Matuk, Arnulfo (Advances in Social Sciences Research Journal, 2021)
One of the main actors worldwide to reduce the effects of the Covid-19 pandemic has been the health personnel of the different health systems. In Mexico, according to what was stated by the Federal Government, by the end of August 2020, 97 thousand 632 cases of health sector workers infected by the SARS - CoV-2 virus had been confirmed and another 10 thousand 933 cases were in quality of suspects, pending the result of laboratory tests. As of this same date, in the country there were a total of 568 thousand 621 people who had had the disease and 61 thousand 450 cases of people who died as a result of this condition.